Tiga Jalan Islam Politik di Indonesia: Reformasi, Refolusi dan Revolusi - Mohammad Iqbal Ahnaf (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2016)
Indonesia is often deemed unfavorable for political Islamic movements. This is prominently indicated by the fact that electoral achievement of parties with Islamic background has been historically lower than those of parties without stated association with Islamic groups. This is seen as a confirmation of the norm that Indonesian Islam is inherently moderate. This paper challenges such an argument because the up and down of political Islamc should not be primarily seen from thir electoral gains. This paper shows that political Islam in Indonesia is persistent and will continue posing a challenge to the dominant role of moderate Islam. Using different paths Islamist groups are competing for establishing ground in societies. This paper categorizes the paths chosen by political Islam in Indonesia into three models called reformist, ‘refolutionist,’ and ‘staged revolutionary.’ Islamic groups are categorized in the paper based on their political objectives and strategies.